VIOLÊNCIA OBSTÉTRICA: PERCEPÇÃO DOS PROFISSIONAIS DE ENFERMAGEM ACERCA DO CUIDADO - Santos, Amália Lúcia Machry (2016)
Obstetric care is one that provides care, support, and protection with the minimum of interventions needed. The objective of this study was to investigate the knowledge of nursing professionals about obstetric violence in order to construct a guideline book. As specific objectives, this study considered: to identify the types of obstetric violence recognized by nursing professionals and to construct information material on humanized care for pregnant women. The study was carried out from September 2015 to November 2016 through an individual interview with thirty-one nursing professionals, of a maternity, of medium level of complexity, of the central region of the interior of Rio Grande do Sul. Data emerged two thematic categories: obstetric violence practiced by health professionals and the implications for professional practice. Obstetric violence in the interviewees' perception is not respecting the wishes of the expectant mother. This is a subjective situation involving all health professionals. Nursing can incorporate in its practices of care for women, coping and prevention of injuries in situations of violence, allowing the Humanized Childbirth premises to be respected. For this, a booklet was developed for the prevention of Obstetric Violence containing the rights of the pregnant woman in the prepartum, delivery and postpartum, as well as the attributions of the nursing professionals to the nursing care. This theme requires frequent approaches and reflections, through lifelong education, so that more humane and dignified care can occur, capable of generating more security and confidence for nursing professionals to carry out care procedures. It has been observed that obstetrical care without scientific support, which is aggressive and often violates the basic human rights of women, is linked to the current model of childbirth care. Through obstetrical nursing, it is possible to rescue the protagonism and the empowerment of the pregnant woman in the process of gestating and giving birth. This topic requires more studies and the development of new research in this area, in order to allow important decision-making of health professionals and advise in the elaboration of new public policies.